Short-Term High-NaCl Dietary Intake Changes Leukocyte Expression of VLA-4, LFA-1, and Mac-1 Integrins in Both Healthy Humans and Sprague-Dawley Rats: A Comparative Study - Mihalj, Martina; Matić, Anita; Mihaljević, Zrinka; Barić, Lidija; Stupin, Ana; Drenjančević, Ines (Mediators of Inflammation, 2019)
This study is aimed at assessing the effects of a short-term high-salt (HS) diet on the peripheral blood leukocyte (PBL) activation status in healthy rats and young human individuals. Distribution of PBL subpopulations and surface expression of integrins were determined using flow cytometry in 36 men and women on a 7-day low-salt diet (<3.2 g salt/day) immediately followed by a 7-day HS diet (~14 g salt/day) or in Sprague-Dawley (SD) rats (n=24) on a 0.4% NaCl diet (aLS group) or a 4% NaCl diet (aHS group) for 7 days. The aHS group presented with an increased frequency of granulocytes, while the frequency of lymphocytes was reduced. Although in humans HS diet reduced the expression of CD11b(act) integrin on lymphocytes, the frequency of CD11b(act)-bearing cells among all PBL subsets was increased. The aHS group of rats exhibited increased expression of total CD11b/c in granulocytes and CD3 lymphocytes. The expression of CD11a was significantly reduced in all PBL subsets from human subjects and increased in the aHS group. CD49d expression on all PBL subsets was significantly decreased in both humans and rats. In human subjects, we found reduced frequencies of intermediate monocytes accompanied by a reciprocal increase in classical monocytes. Present results suggest that a short-term HS diet can alter leukocytes’ activation status and promote vascular low-grade inflammation.